2009
DOI: 10.1182/blood-2008-04-151712
|View full text |Cite
|
Sign up to set email alerts
|

Triggering TLR7 in mice induces immune activation and lymphoid system disruption, resembling HIV-mediated pathology

Abstract: Chronic immune activation is a major cause for progressive immunodeficiency in human immunodeficiency virus type-1 (HIV) infection. The underlying trigger, however, remains largely unknown. HIV single-stranded RNA is a potent immune activator by triggering Toll-like receptor (TLR) 7/8. Thus, we hypothesized that sustained TLR7 triggering induces chronic immune activation and thereby contributes to progressive immunodeficiency. We used the synthetic compound R848 or a mixture of uridine-rich HIV single-stranded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 58 publications
3
107
1
Order By: Relevance
“…CD4 + T cell reduction during infection has been associated not only with direct viral cytotoxicity (3), but with a more generalized state of chronic immune activation, which contributes to cell loss and to immune dysfunction, ultimately leading to disease progression (4,5). This hypothesis is corroborated by many studies indicating that: 1) during infection the markers of immune activation are increased, and they correlate with a poor prognosis (6-9); 2) proinflammatory cytokines and chemokines are expressed at high levels in the lymphoid organs of SIV-infected macaques and of HIV-1-infected patients (10-12); 3) prolonged immune activation in mice models results in T cell immunodeficiency (13) and in lymphoid architecture disruption (14); and 4) natural hosts of SIV, which despite the high viral load do not progress to AIDS, have a much lower immune activation than that found in pathogenic models of SIV infection (15).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…CD4 + T cell reduction during infection has been associated not only with direct viral cytotoxicity (3), but with a more generalized state of chronic immune activation, which contributes to cell loss and to immune dysfunction, ultimately leading to disease progression (4,5). This hypothesis is corroborated by many studies indicating that: 1) during infection the markers of immune activation are increased, and they correlate with a poor prognosis (6-9); 2) proinflammatory cytokines and chemokines are expressed at high levels in the lymphoid organs of SIV-infected macaques and of HIV-1-infected patients (10-12); 3) prolonged immune activation in mice models results in T cell immunodeficiency (13) and in lymphoid architecture disruption (14); and 4) natural hosts of SIV, which despite the high viral load do not progress to AIDS, have a much lower immune activation than that found in pathogenic models of SIV infection (15).…”
supporting
confidence: 62%
“…In HIV-1-infected patients regardless of therapy and in SIV-infected macaques, migration of Th cells in response to chemotactic stimuli is impaired and is associated with perturbation of actin polymerization. Using an in vivo model (14), we demonstrate that chronic immune activation per se is sufficient to dampen Th cell migration, which can be restored by pharmacological modulation of cytoskeleton activity.…”
mentioning
confidence: 99%
“…It was also reported that circulating pDCs in HIVinfected individuals showed an increase in IFN-a expression. 25 Baenziger et al 26 found an AIDS-like pathology in mice treated with TLR7 ligands. African green monkeys, which are considered to be the natural host of SIVagm, will not progress to AIDS even though they show high viral loads upon SIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…S1A). Activation of the TLR7 pathway also induces a rapid increase of proinflammatory cytokines in the serum (18). To assess the impact of MyD88 deficiency on this systemic response, we analyzed serum cytokine levels 6 h after topical IMQ treatment.…”
Section: Resultsmentioning
confidence: 99%